SOME METABOLIC PROCESSES IN THE PATIENTS WITH LONG-TERM CONSEQUENCES OF MILD TRAUMATIC BRAIN INJURY - Lekomtseva, Ye. (International Journal of Medicine and Medical Research, 2020)
Background. Mild traumatic brain injury (mTBI) leads to disturbance of various metabolic processes significant in pathogenesis of the maintaining of long-term consequences after it. The objective of the research was to analyse changes in the activity of some membrane-associated enzyme markers, which are involved in different redox reactions, reflecting main metabolic processes. Methods. Forty-seven patients with long-term consequences of mTBI, thirty controls were enrolled. The levels of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, lactate dehydrogenase (LDH), gamma-glutamyl transpeptidase were evaluated in sera by gas-liquid chromatograph and calorimetric methods. Results. The study revealed significant changes in metabolic processes observed for alkaline phosphatase and LDH, which were the indicators of membrane and redox processes disturbances, acidosis severity and impaired energy cell metabolism. The averages of LDH level was 662.7 versus 381.9 U/L, in the controls. The disease progression was followed by directly proportional LDH increase reaching very high values in the patients with disease duration more than 15 years (mean ±SD 144.6±16.3 versus 82.6±8.4 U/L, controls p<0.05). The long-term consequences of mTBI were characterized by statistically significant decrease of alkaline phosphatase and positive dependence (p<0.05) of it (r=+0.48) on the disease duration with the averages of alkaline phosphatase level of 152.5±11.21 versus 212.6±9.63 U/L, controls (p<0.01). The significance of changes in membrane-associated enzymes serum levels correlated with development of oxidative stress and metabolic processes dysfunction. Conclusion. In the patients with long-term consequences of mTBI, dysregulation of enzymes activity was detected that might be a marker of nervous system energy impairment and membranes destruction.